Perceived family cohesion and its relationship to ego-strength in late adolescents - Fışıloğlu, Hürol. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1984., 1984)
The aim of the study is to investigate the relationship between the perceived family cohesion level and egostrength of the family member. It was hypothesized that late adolescents whose family cohesion scores are moderate will have high ego-strength and late adolescents whose family cohesion scores are high or low will have low ego-strength. Also related to the hypothesis effects of differed sex and demographic characteristics on perceived family cohesion and ego-strength were examined. The sampling population of the research was composed of 60 male and 60 female students of the language Preparatory School of Bosphorus University ages between 17-23. FACES II was used to measure perceived family cohesion and the Ego-Strength Scale was used to measure ego-strength. As the results of the two way Analysis of Variance on the effect of perceived farmily cohesion on ego-strength and the interaction of sex by perceived family cohesion did not indicate significant results the hypothesis was not supported. However, the effect of sex on ego-strength was found to be significant. Males' ego-strength scores were significantly hiqher than were females' scores. Additional results indicated that income of the family, mother's education, father's education had a significant effect on ego-strength of the subject, and the number of siblings had a significant effect on perceived family cohesion level.
Keywords: Communication in families.; Families.; Ego (Psychology) in adolescence.